Persepsi Anak dan Orang Tua tentang Kualitas Hidup Anak Penderita Diabetes Mellitus Tipe 1 - Nur Agustini; Allenidekania Allenidekania; Meriam Efendi (Universitas Airlangga, 2016)
Introduction: Type-1Diabetes mellitus (T1D) management is important to increase the quality of life in diabetic children. This research aimed to explore and to compare the parents and children perspective in the quality of life related to T1D.Methods: Cross sectional method was used to 35 dyad children (8-18 years old) and their parents. Children have been registered in top referral hospital in Indonesia. They filled the PedsQL® Module Diabetes 3.2 by self-report. Data were analyzed by t-test. The characteristic of respondents consist of the children and parents age, length of being diagnoses with T1D and the number of visit in the last 6 months. Quality of life dimensions were measured in the last month since data collected. It consists of sign and symptom, disease and therapy, T1D management concern related to complication and communication.Results: showed that the children mean age was 13.11 + 2.85 years old compared to parents (41.03 + 8.34 years old). The average length of being diagnoses with T1D was 4.54 +2.87 years and the average number of visit in the last 6 months was 5.8 + 1.79. Total score of quality of life from parents and children perspective were 64.41% + 10.97 and 63.09% + 13.25. Moreover, t-test analysis found that there was significant difference in parent perspective compared to the children perspective regarding quality of life related to T1D.Conclusion: children have relatively lower perception in evaluating their quality of life in T1D compared to the parents. Therefore, it is necessary for nurses to explore the influencing factors as well as coping mechanism related to T1D management so that nurses can develop individual nursing plan to increase the T1D children's quality of life.